Synergistic effect of biosynthesized silver nanoparticles with antibiotics against multi-drug resistance bacteria isolated from children with diarrhoea under five years - Tawfeeq , Shahad M.Tawfeeq; Maaroof , Mohammed N.; Al-Ogaidi, Israa (Iraqi Journal of Science, 2022)
Isolation and identification of bacterial isolates were carried out according to the morphology and biochemical characteristics on one hundred and twenty stool specimens collected from children under five years old via using biochemical tests and Api 20E compact system for further confirmation. Bacterial isolates were distributed as (34.48, 20.68, 5.17,0.86) % for Escherichia coli, Salmonella typhi ,Enterobacter aerogenos, Citrobacter freundii and Hafnia alvei respectively and 9.48 % for each Proteus mirabilis, Pseudomonas aeruginosa and Klebsiella Pneumonia. As well as, 2.58% for both Shigella sonnei and Serratia marcescens. Antibiotic susceptibility test for 116 bacterial isolates was performed towards 20 antibiotics types using disk diffusion method. The results showed dissimilar resistance values towards different antibiotics, ten bacterial isolates were collected for each bacterial species to study their resistance values, the ones with the highest resistance level were selected for further study. Meanwhile, easy and cheap green method using the banana peel extract (BPE) was applied to synthesize silver nanoparticles (AgNPs). Phytochemicals of BPE were screened by standard methods. The results verified the existence of alkaloids, flavonoids, and glycosides in it. These components were act as a reducing agent ,stabilizing and capping agents for AgNO3 with the assistance of the microwave. The successfully preparation of AgNPs was established by ultraviolet-visible spectroscopy, Transmission electron microscopy (TEM), Dynamic light scattering (DLS), Fourier Transform Infrared Spectroscopy (FTIR) and zeta potential analysis. The antibacterial activity of the AgNPs against multidrug resistance (MDR) bacteria were studied by using disk diffusion method. The results showed a considerable effect against MDR isolates. The synergistic effects of biosynthesis AgNPs at different concentrations with different standard antibiotic discs (which were Tobramycin, Chloramphenicol, Nitrofuration, Ampicillin-clavulanic acid and Nalidixic acid) against MDR bacteria were also investigated. The result showed the synergistic action of AgNPs and antibiotics leading to enhance antibacterial activity.